Analysis Of Factors Affecting Employee Loyalty In The Ombudsman Of The Republic Of Indonesia: A Review Of Job Satisfaction, Incentives And Working Conditions - Rinny Dharma Diani; Usep Suhud; Agus Wibowo (Journal of Social Research, 2024)
Employee loyalty is an important aspect that can influence organizational performance and effectiveness. At the Ombudsman of the Republic of Indonesia (ORI), the diversity of employment status, namely ASN (State Civil Apparatus) and permanent employees, presents its own challenges in maintaining the level of employee loyalty. This research aims to analyze the factors that influence employee loyalty at the Ombudsman of the Republic of Indonesia by focusing on three main aspects, namely job satisfaction, incentives and working conditions. This study used qualitative research methods. The data collection technique in this research is literature study and open questionnaires. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that employee loyalty at ORI has different employment statuses (ASN and permanent employees), this gives rise to a diverse understanding of the factors that influence employee loyalty. Employee loyalty at ORI is influenced by several factors, namely job satisfaction, incentives and working conditions. In an effort to increase employee loyalty, ORI needs to make efforts to increase job satisfaction, provide incentives and improve working conditions.